PÓLO UNIJUÍ DA REDE ARTE NA ESCOLA: AÇÕES EDUCATIVAS QUE QUALIFICAM O ENSINO DE ARTE DE IJUÍ E REGIÃO - PINHEIRO, ALESANDRA I. D.; JOHANN, MARIA R.; FRANÇOIS, MARLENE R.; PINHEIRO, ALESANDRA I. D.; JOHANN, MARIA R.; FRANÇOIS, MARLENE R.; PINHEIRO, ALESANDRA I. D.; JOHANN, MARIA R.; FRANÇOIS, MARLENE R. (Salão do Conhecimento, 2013)
Resumo